2022
DOI: 10.1002/advs.202203652
|View full text |Cite
|
Sign up to set email alerts
|

Permeability‐Engineered Compartmentalization Enables In Vitro Reconstitution of Sustained Synthetic Biology Systems

Abstract: In nature, biological compartments such as cells rely on dynamically controlled permeability for matter exchange and complex cellular activities. Likewise, the ability to engineer compartment permeability is crucial for in vitro systems to gain sustainability, robustness, and complexity. However, rendering in vitro compartments such a capability is challenging. Here, a facile strategy is presented to build permeability‐configurable compartments, and marked advantages of such compartmentalization are shown in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Semi-permeable hydrogels [ 28 ] or microcapsules [ 29 ] are another state-of-the-art approach for controlling the biochemical reactions within micro-compartments. In these systems, the different reagents smaller than the pore size can diffuse into micro-compartments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-permeable hydrogels [ 28 ] or microcapsules [ 29 ] are another state-of-the-art approach for controlling the biochemical reactions within micro-compartments. In these systems, the different reagents smaller than the pore size can diffuse into micro-compartments.…”
Section: Resultsmentioning
confidence: 99%
“…The peptide concentration increased only slightly to 34 nM when the incubation was continued for a total of 24 h (Figure S3), which suggested that the peptide delivery was mostly completed in the first 3 h. These results demonstrated the feasibility of using nanodroplets to achieve delivery of medium-sized biomolecules into water-in-fluorinated-oil microdroplets. Semi-permeable hydrogels [28] or microcapsules [29] are another state-of-the-art approach for controlling the biochemical reactions within micro-compartments. In these systems, the different reagents smaller than the pore size can diffuse into micro-compartments.…”
Section: Peptide Delivery and Confirmation Using A Fluorescent Immuno...mentioning
confidence: 99%
“…CFE systems, particularly those based on cell lysates, represent promising platforms for various synthetic biology applications, including therapeutic development 8 , genetic part/circuit prototyping biomanufacturing 7,24 , artificial cell construction 25,26 , natural product biosynthesis [27][28][29] , and biomanufacturing 30,31 . Central to these applications is the need for consistent and efficient protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Relying on the supports of computer science, serine integrases and their att sites could be designed, analyzed, and evolved [121] as variants with diverse properties (e.g., affinity [17,106,122], catalytic efficiency [106,[123][124][125][126], specificity [12,120,127], orthogonality [124,128], and chimerism [129]). Furthermore, other technologies including cell-free protein synthesis [130], microfluidics [131], and artificial cells [132,133] will support the research of serine integrases (or tyrosine recombinases) in different synthetic biology applications.…”
Section: Discussionmentioning
confidence: 99%